IDENTIFIKASI SESAR AKTIF DI SEPANJANG JALUR KALI GARANG, SEMARANG - Hidayat, E (Jurnal Geologi dan Sumberdaya Mineral, 2013)
The Semarang area, located in the northen part of Jawa, is an stable area to the subduction earthquake. There fore the active faults, that are originated from the earthquake, have to be concerned. On the landsat imagery there are some lineaments in the Semarang area meanwhile in the field there are some fault including morphotectonic and geological structure features. The morphotectonic features consist of escarpment, and creeping several segments of Garang River, and geological structure features are offset lithology, dragfold and joint in Quaternary rocks of Damar Formation. Based on analysis of the data, the north-south Kali Garang fault indictes an active fault.Keyword: semarang, geological structure, Kali Garang fault, active fault